Pervasive prophage recombination occurs during evolution of spore-forming Bacilli - Dragoš, Anna; Priyadarshini, B.; Hasan, Zahraa; Strube, Mikael Lenz; Kempen, Paul J.; Maróti, Gergely; Kaspar, Charlotte; Bose, Baundauna; Burton, Briana M.; Bischofs-Pfeifer, Ilka; Kovács, Ákos T. (The ISME journal, 2021)
Phages are the main source of within-species bacterial diversity and drivers of horizontal gene transfer, but we know little about the mechanisms that drive genetic diversity of these mobile genetic elements (MGEs). Recently, we showed that a sporulation selection regime promotes evolutionary changes within SPβ prophage of Bacillus subtilis, leading to direct antagonistic interactions within the population. Herein, we reveal that under a sporulation selection regime, SPβ recombines with low copy number phi3Ts phage DNA present within the B. subtilis population. Recombination results in a new prophage occupying a different integration site, as well as the spontaneous release of virulent phage hybrids. Analysis of Bacillus sp. strains suggests that SPβ and phi3T belong to a distinct cluster of unusually large phages inserted into sporulation-related genes that are equipped with a spore-related genetic arsenal. Comparison of Bacillus sp. genomes indicates that similar diversification of SPβ-like phages takes place in nature. Our work is a stepping stone toward empirical studies on phage evolution, and understanding the eco-evolutionary relationships between bacteria and their phages. By capturing the first steps of new phage evolution, we reveal striking relationship between survival strategy of bacteria and evolution of their phages.